Green Peach Aphid, Myzus persicae (Sulzer) (Insecta: Hemiptera: Aphididae) - John L. Capinera (EDIS)
The green peach aphid, Myzus persicae (Sulzer), is found throughout the world, including all areas of North America, where it is viewed as a pest principally due to its ability to transmit plant viruses. In addition to attacking plants in the field, green peach aphid readily infests vegetables and ornamental plants grown in greenhouses. This allows high levels of survival in areas with inclement weather, and favors ready transport on plant material. When young plants are infested in the greenhouse and then transplanted into the field, fields will not only be inoculated with aphids but insecticide resistance may be introduced. These aphids also can be transported long distances by wind and storms.  This document is EENY-222, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: July 2001. Revised: July 2004.